Slovenci v Združenih državah - Stanonik, Janez (Dve domovini, 1996)
The study gives initially a statistical analysis of Slovene emigration to the United States in the second half of the 19th century. The author gives an analysis of the social situation and political affiliations of Slovene immigrants as revealed by the Slovene fraternal organizations they began to form in the States. Since the 70's we can also register the first book published specially for the needs of Slovene emigrants in the United States, giving information about the English language, American institutions and economic conditions.
Keywords: 1848-1891; družbeni položaj; Slovenci; Slovenes; slovenski izseljenci; United States of America; ZDA